Changes in the climate conditions of the Volga Federal District during the 19th – 21st centuries - L.V. Shaikhulmardanova; V.V. Guryanov; Yu.P. Perevedentsev (Учёные записки Казанского университета: Серия Естественные науки, 2018)
The possibility to reproduce the surface air temperature using the climatic models of the CMIP5 projects has been discussed. Potential changes in the air temperature of the Volga Federal District (VFD) for the 21st century have been assessed based on an ensemble of 35 climatic models. The results of the calculations have demonstrated that the air temperature is expected to increase if the scenario of moderate anthropogenic impact (RCP4.5) on the VFD climatic system in the 21st century holds true. The air temperature growth is likely to increase during the winter and summer periods. In this case, the intensity of winter warming will be higher. The analysis of the amplitude and phase first harmonic of the annual fluctuations in the surface air temperature has been performed.